O Menir dos Penedos da Portela, em Portela das Cabras, Vila Verde, Noroeste de Portugal - Bettencourt, Ana M. S. (2021)
Presentation of the Penedos da Portela menhir (Vila Verde, Braga), mentioned since the end of the 19th century and re-located in 1994 and 2007 by two of the authors, after archaeological survey work carried out for the archaeological inventory of the Vila Verde municipality. The menhir is probably in situ and marks one of the natural entrances to the Megalithic necropolis of the Montes do Borrelho and Moinho Velho. It appears to have been partially smoothed on the west and south sides, from top to bottom, giving it the appearance it has today.